The shape of the socioeconomic– oral health gradient: implications for theoretical explanations - Sanders AE, Slade GD, Turrell G, John Spencer A, Marcenes W. (Blackwell Synergy, 2006)
The nature of the relationship between status and health has theoretical and applied significance.